2019
DOI: 10.1186/s40008-019-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

Internet usage, innovation and human development nexus in Africa: the case of ECOWAS

Abstract: This study is set out to examine the influence of internet usage and innovation in enhancing human development in Economic Community of West African States (ECO-WAS) countries. It tests the consistency of literature with the experience of ECOWAS countries, thus investigating the nature of the relationship between Internet adoption, innovation and human development. The objectives of the study are essential as the advent of Internet technology signalled the birth of a revolution that would later prove to be a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 21 publications
4
30
0
2
Order By: Relevance
“…The results suggest a positive relationship between innovation performance and human development. This result is in line with the finding of Ejemeyovwi, Osabuohien, Johnson (2019) which found that innovation has a significant and positive relationship with human development in Africa. However, this result contradicts the findings of Silva & Moreira (2019) which not confirmed the relationship between innovation and human development.…”
Section: Discussionsupporting
confidence: 91%
“…The results suggest a positive relationship between innovation performance and human development. This result is in line with the finding of Ejemeyovwi, Osabuohien, Johnson (2019) which found that innovation has a significant and positive relationship with human development in Africa. However, this result contradicts the findings of Silva & Moreira (2019) which not confirmed the relationship between innovation and human development.…”
Section: Discussionsupporting
confidence: 91%
“…Internet usage being the main independent variable tested for statistical significance in Model 1also revealed to have a significant and positive association with HDI, thus indicating that high levels of Internet usage are crucial in improving human development of the countries. This evidence supports findings by De La Hoz et al 2019, Ejemeyovwi et al (2019) and Çaglayan-Akay and Van (2017) who all found similar significant and positive relationship between Internet usage and human development. This study found that 1 percent increase in the share of population using the Internet is associated with a 0.0009 increase in the HDI value.…”
Section: Business and Economic Researchsupporting
confidence: 90%
“…The study expressed growth as a function of institutions, technology, and other growth components. The model explains that for growth in human development to be achieved, a number of factors must be present such as institutions, technology adoption, and innovation alongside the necessary control variables as initially emphasized by Ejemeyovwi, Osabuohien, Johnson, et al (2019).…”
Section: The Empirical Modelmentioning
confidence: 99%